The Relationship between Malnutrition and Quality of Life in Stable Chronic Obstructive Pulmonary Disease Patients at Prof. Dr. Chairuddin P. Lubis Hospital Field - Dalimunthe, Muhammad Bayhaqi; Pradana, Andika; Tarigan, Amira Permatasari; Amelia, Rina (CoinReads Media Prima, 2024)
Introduction: Malnutrition is a serious problem in patients with COPD, it interferes with normal skeletal muscle function, with reduced muscle mass and decreased respiratory muscle strength and endurance. It also contributes to respiratory muscle dysfunction, disease severity, and disability progression. Malnutrition is associated with disease severity, associated with more severe exacerbations, and increases the length of hospital stay. Malnutrition in COPD is described with varying prevalence rates ranging from 30-60%. The aim of this study was to analyse the relationship between malnutrition and quality of life in patients with COPD. Method: The research design is an observational analytic conducted from November 2023 to March 2024. The study population was COPD patients who sought treatment at the Pulmonary Polyclinic at RSCPL with a total sample using the consecutive sampling method of 91 people. Manultrition assessment by measuring TB and BW of patients when they arrived and assessing quality of life with the SGRQ questionnaire, Data processing using SPSS by correlating malnutrition with quality of life, degree of shortness of breath, and spirometry. Results: There was a significant positive correlation between malnutrition and quality of life (p=0.001) with the degree of shortness of breath (p=0.014) and spirometry (p=0.001). Conclusion: We found an association between malnutrition and quality of life, degree of breathlessness and spirometry of patients with COPD, further prospective studies in other populations are needed to validate the results of this study.